Writing Moroccan Space: A Comparative Study of Anaïs Nin’s “The Labyrinthine City of Fez” and George Orwell’s “Marrakech” - Dahman, Abdeghni (International Journal of Linguistics, Literature and Translation, 2026)
Unlike novels and plays, Western short travel narratives about Morocco have received little scholarly attention. This paper seeks to interrogate the representation of Moroccan spatiality in two such works: Anaïs Nin’s “The Labyrinthine City of Fez” and George Orwell’s “Marrakech.” Through a comparative approach that moves beyond conventional binary oppositions, the study explores the evolving portrayals of Morocco in Western short travelogues. It argues that Western conceptualizations of Morocco are far from uniform; rather, they are heterogeneous, marked by contradictions and slippages. In these narratives, Morocco alternately emerges as an emotional sanctuary and a visually arresting space of architectural refinement, or as a site burdened by decay and deprivation. I contend that the depiction of Moroccan spatiality in these short accounts is characterized by multiplicity and, at times, conflicting narrative perspectives. Such diversity produces a more nuanced Western attitude toward Morocco, which resists being simply categorized as purely Orientalist.